The Role of Place in Fostering Belonging and Science Identity Development for Incoming Ecology and Evolutionary Biology Graduate Students: Perspectives From a Two‐Year Program Evaluation - Sriparna Saha; Valerie McKenzie; Nancy Emery; Julian Resasco; Scott Taylor; Sandhya Krishnan; Lisa A. Corwin (Ecology and Evolution)
ABSTRACT As graduate students transition into advanced academic environments, the physical and social contexts in which they engage play a critical role in shaping their sense of belonging, academic success, and personal development. Using a qualitative approach, this study explores how an immersive and place‐based fieldwork program impacted community building and self‐efficacy in incoming graduate students in an Ecology and Evolutionary Biology (EEB) program. Data were collected through surveys, focus groups, and in‐depth interviews with students over the program's duration. Our findings reveal that the remote location of the program played an important role in community development and fostered autonomy and competence. We also found that choosing a discipline‐focused location for fieldwork can positively impact student experiences. Opportunities for interdisciplinary collaboration and mentorship emerged as key components of fostering a supportive academic community. The study demonstrates a positive role for place‐based strategies in graduate program design, suggesting that creating spaces that nurture collaboration, allow students to enact disciplinary skills, and present students with formative challenges can enhance academic resilience and self‐confidence. The findings offer implications for institutions looking to cultivate stronger, more cohesive graduate communities and for future research on the intersection of place, identity, and academic success in higher education.